FIXED POINT AND MEAN CONVERGENCE THEOREMS FOR A FAMILY OF λ-HYBRID MAPPINGS - Aoyama, K.; Kohsaka, F. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2011)
The aim of this paper is to prove fixed point and mean convergence theorems for a sequence of λ-hybrid mappings in Hilbert spaces.